Risk factors for gastroesophageal reflux disease symptoms related to lifestyle and diet - Anna Taraszewska (National Institute of Public Health - National Institute of Hygiene, 2021)
Gastroesophageal reflux disease (GERD) is one of the most common diseases of the upper gastrointestinal tract. The most characteristic symptom of the disease is heartburn, which occurs at least once a week. The prevalence of the disease varies and, depending on the region of the world, it may affect from a few to over 30% of an adult population. It is estimated that in Poland this disease may affect up to 35.5% of adults reporting abdominal ailments. If untreated, the disease can lead to serious complications including precancerous conditions and esophageal adenocarcinoma. Pharmacotherapy is considered as the first-line treatment in GERD patients but lifestyle modifications, including diet changes, are an important element supporting the treatment of the disease. Many factors may contribute to the development of the disease. Among them, there are non-modifiable factors such as age, sex or genetic factors and modifiable factors, e.g. lifestyle, diet, excessive body weight. This review focuses on GERD risk factors related to lifestyle and nutrition that include both dietary components and nutritional behaviour. Lifestyle risk factors that may contribute to GERD symptoms include excessive body weight, particularly obesity, moderate/high alcohol consumption, smoking, postprandial and vigorous physical activity, as well as lack of regular physical activity. Many studies indicate fatty, fried, sour, spicy food/products, orange and grapefruit juice, tomatoes and tomato preserves, chocolate, coffee/tea, carbonated beverages, alcohol as triggers for GERD symptoms. Eating habits such as irregular meal pattern, large volume of meals, eating meals just before bedtime may correlate with the symptoms of GERD. The role of lifestyle, diet and eating habits as risk factors for GERD is not clearly understood, and the results of the available studies are often contradictory. Determination of modifiable risk factors for this disease and its symptoms is important for effective dietary prevention and diet therapy of GERD.